The Role of Clonal Evolution on Progression, Blood Parameters, and Response to Therapy in Multiple Myeloma - Sandmann, Sarah; Karsch, Katharina; Bartel, Peter; Exeler, Rita; Brix, Tobias J.; Mai, Elias K.; Varghese, Julian; Lenz, Georg; Khandanpour, Cyrus (Frontiers in Oncology, 2022)
Introduction: A variety of biomarkers are considered for diagnosis (e.g. β2-microgobulin, albumin or LDH) and prognosis (e.g. cytogenetic aberrations detected by FISH) of multiple myeloma (MM). More recently, clonal evolution has been established as key. Little is known on clinical implications of clonal evolution. Methods: We performed in-depth analyses of 25 patients with newly diagnosed MM with respect to detailed clinical information analyzing blood samples collected at several time points during follow-up (median follow-up: 3.26 years since first diagnosis). We split our cohort into two subgroups: with and without new FISH clones developing in the course of disease. Results: Each subgroup showed a characteristic chromosomal profile. 43% of patients had evidence of appearing new clones. The patients with new clones showed an increased number of translocations affecting chromosomes 14 (78% vs 33%; p=0.0805) and 11, and alterations in chromosome 4 (amplifications and translocations). New clones, on the contrary, were characterized by alterations affecting chromosome 17. Subsequent to development of the new clone, 6 out of 9 patients experienced disease progression compared to 3 out of 12 for patients without new clones. Duration of the therapy applied for the longest time was significantly shorter within the group of patients developing new clones (median: 273 vs 406.5 days; p=0.0465). Discussion: We demonstrated that development of new clones, carrying large-scale alterations, was associated with inferior disease course and shorter response to therapy, possibly also affecting progression free survival and overall survival. Further studies evaluating larger cohorts are necessary for validation of our results.